Detection of circumstellar helium in Type Iax progenitor systems. Issue 2 (14th May 2019) - Jacobson-Galán, Wynn V; Foley, Ryan J; Schwab, Josiah; Dimitriadis, Georgios; Dong, Shawfeng; Jha, Saurabh W; Kasen, Daniel; Kilpatrick, Charles D; Thomas, Rollin
ABSTRACT: We present direct spectroscopic modelling of 44 Type Iax supernovae (SNe Iax) using spectral synthesis codeSYNAPPS . We confirm detections of helium emission in the early-time spectra of two SNe Iax: SNe 2004cs and 2007J. These He i features are better fit by a pure-emission Gaussian than by a P-Cygni profile, indicating that the helium emission originates from the circumstellar environment rather than the SN ejecta. Based on the modelling of the remaining 42 SNe Iax, we find no obvious helium features in other SN Iax spectra. However, ${≈ } 76{{\ \rm per\ cent}}$ of our sample lack sufficiently deep luminosity limits to detect helium emission with a luminosity of that seen in SNe 2004cs and 2007J. Using the objects with constraining luminosity limits, we calculate that 33 per cent of SNe Iax have detectable helium in their spectra. We examine 11 SNe Iax with late-time spectra and find no hydrogen or helium emission from swept-up material. For late-time spectra, we calculate typical upper limits of stripped hydrogen and helium to be 2 × 10 −3 M⊙ and 10 −2 M⊙, respectively. While detections of helium in SNe Iax support a white dwarf–He star binary progenitor system (i.e. a single-degenerate [SD] channel), non-detections may be explained by variations in the explosion and ejecta material. The lack of helium in the majority of our sample demonstrates the complexity of SN Iax progenitor systems and the need for further modelling. With strong independent evidence indicating that SNe Iax arise from an SD channel, we caution the common interpretation that the lack of helium or hydrogen emission at late-time in SN Ia spectra rules out SD progenitor scenarios for this class.